Reporting and Selling the Agricultural Research Story - Mason E. Miller (Journal of Applied Communications, 1979)
Science communication - he reporting of the outcomes of science, the process of science, and of events in science and about science that are important to others to know - tends to take a backseat in some land-grant university information units. But that may be changing. (Papers from the National Agricultural Science Information Conference, Ames, Iowa.)